Роль ліпоцитокінів у патогенезі метаболічного синдрому - Щекатурова, Л. В.; Ларін, О. С.; Кирилюк, М. Л.; Третяк, О. Е.; Підаєв, А. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
The data concerning the metabolic syndrome and its clusters, role of lipocytocins and insulin resistance at different stages of development of type 2 diabetes are presents in the review.